BEREKONOMI DAN BERTRANSAKSI DENGAN ATURAN SYARIAH - Fatmawati Sungkawaningrum; Nashih Muhammad (Program Studi Perbankan Syariah, 2020)
In this world Allah SWT creates and provides everything for us human beings. Whatever things that humans need are available in this universe. In the development of human life that is equipped with this lust, of course, have desires and goals. There are various forms and norms and ways to live it as a human being. We expect to always get what we want, and get what we aspire to. Various aspects of the road and ways to go through it. In front of us there are many paths to choose from which we will pass, and there are many people who have built the road. Anyone who will pass directly and indirectly will follow from any rules and burdens that can pass that road. What is meant by the road is the rule of the architect who made or built the road. Will choose a conventional path or, choose the path according to Islamic sharia. Clearly the concept is that there are differences between the two road rules. The purpose of this paper is to build awareness in the community for the development of quality human resources and philanthropic practices so that the practice of usury in the community can be eroded. The methodology of this research is literature study and observations in the community. Muslims have been provided a way of creation of Allah SWT, but the way is in the form of an essential concept that is the Islamic economic concept that prohibits the element of riba in it.